Rancang Bangun Sistem Smart Door Lock Menggunakan Mikrokontroler Esp32 Berbasis Internet Of Things (Iot) dan Smartphone Android - Maulana, Ikhlas; Azriadi, Emon; Musrido, Joko (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
This study aims to design and build smart door lock system using Microcontroller ESP32 based on Internet of Things (IoT) and Smartphone Android which will be installed in one of the study rooms at Pahlawan Tuanku Tambusai University using the Quality Function Deployment (QFD) method which aims to identify and meet the needs and desires of consumers for the resulting product or service. This smart door lock is specially made to improve the security system more optimally, and transforming the use from manual door locks to smart door locks that more ergonomic in following technological developments and advances and expanding the use of internet networks in the field of security systems. The process of manufacture smart door locks based on consumer desires using the QFD method which has been processed using the house of quality (HoQ). it can be seen that the percentage of the highest value or priority for product attributes is “Control the smart door lock system using a smartphone” with a value presentation of 5,643%, followed by “Access the smart door lock using the internet network"with a value of 5,479%, Then on the third priority, “Smart door lock system accurately accepts input commands” with a value of 5,226%. Smart door lock product specifications based on the voice of customer statement are that in the main function of the smart door lock system can be controlled using a smartphone with blynk application control software via the internet network, then to meet the wishes of consumers provided wifi module on system components, or the durability of the door lock lever (solenoid) made of steel coated with stenliss so that it is not easily break in, as well the aesthetics (design) of smart door locks using PVC Box as a hardware display, and equipped with alarm as indication of sound when the smart door lock system is successfully accessed.